Race and Sex Disparities in Prehospital Recognition of Acute Stroke. (25th February 2015) - Govindarajan, Prasanthi; Friedman, Benjamin T.; Delgadillo, James Q.; Ghilarducci, David; Cook, Lawrence J.; Grimes, Barbara; McCulloch, Charles E.; Johnston, S. Claiborne; Callaway, Clifton
Abstract Objectives The objective of this study was to examine prehospital provider recognition of stroke by race and sex. Methods Diagnoses at emergency department (ED) and hospital discharge from a statewide database in California were linked to prehospital diagnoses from an electronic database from two counties in Northern California from January 2005 to December 2007 using probabilistic linkage. All patients 18 years and older, transported by ambulances (n = 309, 866) within the two counties, and patients with hospital‐based discharge diagnoses of stroke (n = 10, 719) were included in the study. Logistic regression was used to analyze the independent association of race and sex with the correct prehospital diagnosis of stroke. Results There were 10, 719 patients discharged with primary diagnoses of stroke. Of those, 3, 787 (35%) were transported by emergency medical services providers. Overall, 32% of patients ultimately diagnosed with stroke were identified in the prehospital setting. Correct prehospital recognition of stroke was lower among Hispanic patients (odds ratio [OR] = 0.77, 95% confidence interval [CI] 0.61 to 0.96), Asians (OR = 0.66, 95% CI 0.55 to 0.80), and others (OR = 0.71, 95% CI = 0.53 to 0.94), when compared with non‐Hispanic whites, and in women compared with men (OR = 0.82, 95% CI = 0.71 to 0.94). Specificity for recognizing stroke was lower in females than males (OR = 0.84, 95% CI = 0.78 to 0.90). Conclusions Significant disparities exist in prehospital stroke recognition.